Pengenalan Model Bisnis Untuk Meningkat Daya Saing UMKM Di Nagari Gasan Gadang Kabupaten Padang Pariaman - Yentisna Yentisna; Alfin Alvian; Prima Yulianti; Masruri Masruri; Tiara Turay (Jurnal Pengabdian Masyarakat Dharma Andalas, 2023)
Entrepreneurship is a universal thing that can be done, including MSMEs, MSMEs should receive tips for good entrepreneurship from an early age. Entrepreneurship certainly does not only talk about theoretical matters but also the application of the knowledge of entrepreneurship that has been studied. Some MSMEs currently have entrepreneurial knowledge in their business processes, but this process has not been able to optimally encourage MSMEs to create a business idea that is poured into a business proposal. The purpose of this activity is to equip MSMEs in Nagari Gasan, Padang Pariaman Regency, who have an entrepreneurial spirit so they can understand and apply their business ideas using the right methods. The debriefing is carried out by introducing a business planning method, namely the Business Model Canvas (BMC). The Business Model Canvas as a strategy in management in the form of a visual chart consisting of 9 elements can provide a more comprehensive picture of business planning but is relatively easier to understand and apply. Through the introduction of the Business Model Canvas, it is hoped that MSMEs can translate and apply their business ideas into these 9 elements in a more structured and detailed manner, thus facilitating the process of preparing the right business proposals for MSMEs.